Two-to-one color-response mapping and the presence of semantic conflict in the Stroop task - Hasshim, Nabil; Parris, Benjamin A. (Frontiers in Psychology, 2014)
A series of recent studies have utilised the two-to-one mapping paradigm in the Stroop task. In this paradigm, the word red might be presented in blue when both red and blue share the same response key (same-response trials). This manipulation has been used to show the separate contributions of (within) semantic category conflict and response conflict to Stroop interference. Such results evidencing semantic category conflict are incompatible with models of the Stroop task that are based on response conflict only. However, the nature of the same-response trials is unclear since they are also likely to involve response facilitation given that both dimensions of the stimulus provide evidence towards the same response key. In this study we explored this possibility by comparing them with three other trial types. We report strong (Bayesian) evidence for no statistical difference between same-response and non-colour word neutral trials, faster responses to same-response trials than to non-response set incongruent trials, and no differences between same-response vs. congruent trials when contingency is controlled. Our results suggest that when RT is the dependent variable, same-response trials are not different from neutral trials indicating that they cannot be used reliably to determine the presence or absence of semantic category conflict. In light of these results, the interpretation of a series of recent studies might have to be reassessed.